Persistence of Two Non-Saccharomyces Yeasts (Hanseniaspora and Starmerella) in the Cellar - Grangeteau, Cédric; Gerhards, Daniel; von Wallbrunn, Christian; Alexandre, Hervé; Rousseaux, Sandrine; Guilloux-Benatier, Michèle (Frontiers in Microbiology, 2016)
Different genera and/or species of yeasts present on grape-berries, in musts and wines are widely described. Nevertheless, the community of non-Saccharomyces yeasts present in the cellar is still given little attention. Thus it is not known if the cellar is a real ecological niche for these yeasts or if it is merely a transient habitat for populations brought in by grape-berries during the winemaking period. This study focused on three species of non-Saccharomyces yeasts commonly encountered during vinification: Starmerella bacillaris (synonymy with Candida zemplinina), Hanseniaspora guilliermondii and Hanseniaspora uvarum. More than 1200 isolates were identified at the strain level by FT-IR spectroscopy (207 different FTIR strain pattern). Only a small proportion of non-Saccharomyces yeasts present in musts came directly from grape-berries for the three species studied. Some strains were found in the must in 2 consecutive years and some of them were also found in the cellar environment before the arrival of the harvest of second vintage. This study demonstrates for the first time the persistence of non-Saccharomyces yeast strains from year to year in the cellar. Sulfur dioxide can affect yeast populations in the must and therefore their persistence in the cellar environment.